The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.apsusc.2012.11.069
|View full text |Cite
|
Sign up to set email alerts
|

Plasma diagnostics in pulsed laser deposition of GaLaS chalcogenides

Abstract: The aim of this work is to characterize the ejection plume obtained by laser ablation of GaLaS (GLS) samples in order to better understand the ablation phenomena for optimizing the pulsed laser deposition of chalcogenide thin films. The dynamics of the plasma between target and substrate was investigated through timeand space-resolved optical emission spectroscopy. High-resolution optical spectra have been recorded in the UV-VIS range using a 500-mm focal length monochromator and a fast gate ICCD camera. From … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
(34 reference statements)
2
10
0
Order By: Relevance
“…For our experiments the resulting glass rods (25 mm in diameter) were sliced and polished. In order to study the laser ablation process on the chalcogenide glasses the experimental set-up shown in Figure 1 was employed [24,25]. The experiments were performed in a stainless steel vacuum chamber at a residual pressure of 10 -6 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…For our experiments the resulting glass rods (25 mm in diameter) were sliced and polished. In order to study the laser ablation process on the chalcogenide glasses the experimental set-up shown in Figure 1 was employed [24,25]. The experiments were performed in a stainless steel vacuum chamber at a residual pressure of 10 -6 Torr.…”
Section: Methodsmentioning
confidence: 99%
“…Such double-structures are often reported in the literature for both fs-and ns-laser ablation, being observed for plume propagating in an ambient gas [14,15,20,88] and in vacuum for high-fluence irradiation [56,57,67,75]. Reports from literature usually present a difference of one order of magnitude between the expansion velocities of the two plasma components.…”
Section: Resultsmentioning
confidence: 84%
“…Based on our previous ICCD fast camera imaging and space-and time-resolved optical emission spectroscopy measurements, we know that these times are characteristic for the observation of the slow plasma component [55,56,67]. As expected, it resulted that all studied parameters have a significant space-time decrease, due to the cooling process and rarefaction during expansion ( Figure 7).…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The thickness of the above layered materials was in the micrometer scale, which was applied for the optical devices. Gurlui et al reported that the GaLaS, Er‐doped GaLaS, and Er/Pr codoped GaLaS glass thin films with the thickness in the micrometer scale have been prepared by the PLD approach (Figure ‐F). These glass films were all amorphous chalcogenides, and the increased temperature of substrate enhanced the crystallinity of the films.…”
Section: Materials Classification and Synthesismentioning
confidence: 99%